Here or there, who do you trust? Patterns of social trust following the migration experience of Romanians in Spain and France - Birou Mara (Social Change Review, 2023)
This paper links the concept of social trust and that of migration by exploring the interactions and dependencies between Romanian emigrants and returnees and various institutional and social actors. Consequently, the underlying question of the research is: ‘What are the ways in which migration experience is associated with social trust?’. This research discusses how experiences with public agencies in Romania or in the host country determine trust or conversely, induce the feeling of distrust. Common specific elements were taken into account, such as determinants and effects of trust, life experience as immigrants, level of integration, and level of satisfaction or dissatisfaction with public entities, which linked empirically the two concepts. Drawing on a set of interviews with Romanian emigrants and Romanian returnees1, this research tackles the peculiarities of emigrants’ and returnees’ experiences as key factors in identifying the levels of social trust.